2019
DOI: 10.1007/s00431-019-03521-6
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cardiac hypertrophy: the role of hyperinsulinism—a review of literature

Abstract: Hypertrophic cardiomyopathy (HCM) in neonates is a rare and heterogeneous disorder which is characterized by hypertrophy of heart with histological and functional disruption of the myocardial structure/composition. The prognosis of HCM depends on the underlying diagnosis. In this review, we emphasize the importance to consider hyperinsulinism in the differential diagnosis of HCM, as hyperinsulinism is widely associated with cardiac hypertrophy (CH) which cannot be distinguished from HCM on echocardiographic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 109 publications
0
40
0
3
Order By: Relevance
“…A meta-analysis of 39 studies showed that fetuses of both PGDM and GDM pregnancies had in the third trimester increased intraventricular septal thickness compared to controls [ 196 ]. A literature review found an incidence ranging from 13% to 44% among asymptomatic and symptomatic neonates [ 197 ]. El-Ganzoury et al found a correlation between poor maternal glycemic control (HbA1c ≥ 7%) and interventricular septal thickness [ 198 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…A meta-analysis of 39 studies showed that fetuses of both PGDM and GDM pregnancies had in the third trimester increased intraventricular septal thickness compared to controls [ 196 ]. A literature review found an incidence ranging from 13% to 44% among asymptomatic and symptomatic neonates [ 197 ]. El-Ganzoury et al found a correlation between poor maternal glycemic control (HbA1c ≥ 7%) and interventricular septal thickness [ 198 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…It has been shown that hyperinsulinemia was associated with cardiac hypertrophy in neonates. 26 A study in db/db mice suggested that systemic hyperinsulinemia contributed to cardiac hypertrophy, which could be blocked by the deletion of insulin-like growth factor-1R. 27 Continuous administration of insulin for 7 weeks using osmotic pumps increased LV mass and relative wall thickness in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Определение «гипертрофическая кардиомиопатия» нередко встречается в научных статьях, посвященных влиянию СД матери в период беременности на сердце плода и новорожденного. Другие исследователи оспаривают правомерность использования данного термина в отношении детей от матерей с СД [30]. Это связано с тем, что гиперинсулинизм ассоциирован с гипертрофией сердца, но возникающие изменения не соответствуют критериям гистологических и функциональных нарушений, необходимых для постановки диагноза ГКМП.…”
unclassified
“…Это, вероятно, является следствием разнородности с точки зрения отбора пациентов (СД1, СД2 и ГСД), степени компенсации уровня глюкозы у матери, времени исследования и, что немаловажно, опыта специалиста, проводившего эхокардиографическое исследование (ЭХО-КГ) (табл. 4) [30]. Несколько исследований продемонстрировали связь между формированием гипертрофии сердца у детей и типом материнского диабета.…”
unclassified
See 1 more Smart Citation